Preconception Health of Prospective Brides and Grooms in Malang Regency, Indonesia - Tazkiyah, Nadya Dina; Suprapti, Suprapti; Wulandari, Lisa Purbawaning; Sunaeni, Sunaeni; Mansur, Herawati (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Preconception health is a significant contributor to pregnancy outcomes. However, the majority of women only improve their health status after receiving counseling at the first antenatal visit or during pregnancy. This shows the need to identify preconception health through premarital screening. Therefore, this study aimed to assess the characteristics of preconception health of prospective brides in Malang Regency using